Cairo declaration of human rights: viability as an Islamic alternative declaration - Haneef, Sayed Sikandar Shah (2013)

(untitled)
Cairo declaration represents the official response from Muslim states to UNDH 1948. There are many points of contrast between the two in spite of some similarities in terms of content. This paper reviews those points with offering academic answer for more effective response.